Perception of justice, privacy, and validity when using social media as an evaluation tool in hiring - Sonja M. Júlíusdóttir Jacobsen 1996- (2022)
Screening applicants’ social media to evaluate them and make hiring decisions seems to be increasingly used as a method of personnel selection among those overseeing hiring. In Iceland, evidence shows that social media screening is applied in a third of hiring instances, and employers have claimed that it is an invaluable tool that provides them with an unfiltered view of applicants, something that may prove difficult using other assessment methods. The problem with social media screening is that the method is an unstandardized approach, and social media frequently offers more information about applicants than those overseeing hiring originally intended to find. This can increase the likelihood of bias or negative assumptions being made about applicants that could influence hiring decisions. Furthermore, the method has been proven to be weak in terms of validity and reliability, alongside its current lack of soundness as an indicator of job performance. From the applicants’ perspective, literature and research indicate that they have a negative perception of screening social media for hiring decisions in a professional setting. To observe how people in Iceland perceive the personnel selection tool, a three-factor scale, focusing on justice, privacy, and validity, was used by manner of an explorative study and its online survey of 305 participants. The current study’s findings correspond with previous studies on applicants’ perception of social media screening as an unfair method that offers an inaccurate representation of them, their personality, and their job competencies. However, the results suggest that applicants’ perception of the method as an invasion of privacy is not as intense in comparison to justice and validity. Still, the findings point to social media screening not being as valuable as employers or recruiters seem to believe, as online profiles on social media platforms are inconsistent and often entertainment-based without regard to employment purposes.